Exploring digital library usage for getting information from the ELM perspective: The moderating effect of information need. Issue 3 (16th May 2016) - Zha, Xianjin; Li, Li; Yan, Yalan; Wang, Qian; Wang, Gang
Abstract : Purpose: – The elaboration likelihood model (ELM) provides a general framework for understanding the basic processes underlying the effectiveness of persuasion. The purpose of this paper is to utilize the ELM to understand the basic processes underlying the effectiveness of persuasion to use digital libraries for getting information. Design/methodology/approach: – The survey data collection was conducted in one comprehensive university. The partial least squares structured equation modelling was employed to verify the research model. Findings: – Source credibility and reputation have positive effects on information usefulness which further significantly impacts digital library usage for getting information. The effect of information quality on information usefulness is overpowered by reputation. Information need positively moderates the effect of information quality on information usefulness and negatively moderates the effect of reputation on information usefulness. Practical implications: – Digital libraries enormously influence the way how individuals gather information over the world. However, the important status of digital libraries as conventional information sources in practice invites appreciation by more and more people. The authors believe the findings of this study provide useful insights for facilitating digital libraries to be fully accessed and utilized. Originality/value: – This study explores the effects of the central route (information quality) and the peripheral route (source credibility and reputation) on digital library usage for getting information by extending the ELM with information need as a motivation variable, presenting a new lens for digital library research and practice alike.